Place of Birth Preferences and Relationship to Maternal and Newborn Outcomes Within the American Association of Birth Centers Perinatal Data Registry, 2007-2020. Issue 2 (April 2022) - Jolles, Diana R.; Montgomery, Tiffany M.; Blankstein Breman, Rachel; George, Erin; Craddock, Jaih; Sanders, Sarah; Niemcyzk, Nancy; Stapleton, Susan; Bauer, Kate; Wright, Jennifer
Abstract : Purpose: The purpose of this study was to describe sociodemographic variations in client preference for birthplace and relationships to perinatal health outcomes. Methods: Descriptive data analysis (raw number, percentages, and means) showed that preference for birthplace varied across racial and ethnic categories as well as sociodemographic categories including educational status, body mass index, payer status, marital status, and gravidity. A subsample of medically low-risk childbearing people, qualified for birth center admission in labor, was analyzed to assess variations in maternal and newborn outcomes by site of first admission in labor. Results: While overall clinical outcomes exceeded national benchmarks across all places of admission in the sample, disparities were noted including higher cesarean birth rates among Black and Hispanic people. This variation was larger within the population of people who preferred to be admitted to the hospital in labor in the absence of medical indication. Conclusion: This study supports that the birth center model provides safe delivery care across the intersections of US sociodemographics. Findings from this study highlight the importance of increased access and choice in place of birth for improving health equity, including decreasing cesarean birth and increasing breastfeeding initiation.